2018
DOI: 10.1038/s41598-018-20409-x
|View full text |Cite
|
Sign up to set email alerts
|

Polygonum aviculare L. extract and quercetin attenuate contraction in airway smooth muscle

Abstract: Because of the serious side effects of the currently used bronchodilators, new compounds with similar functions must be developed. We screened several herbs and found that Polygonum aviculare L. contains ingredients that inhibit the precontraction of mouse and human airway smooth muscle (ASM). High K+-induced precontraction in ASM was completely inhibited by nifedipine, a selective blocker of L-type voltage-dependent Ca2+ channels (LVDCCs). However, nifedipine only partially reduced the precontraction induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
(34 reference statements)
0
16
0
1
Order By: Relevance
“…Specifically, we found that quercetin, kaempferol, and apigenin acted on 172, 106 and 46 targets, respectively, and became the crucial bioactive components in MXGSD. Some studies suggested that quercetin could reduce airway inflammation and relax airway smooth muscle (ASM) by regulating some key pathways, such as mast cell signaling pathway and calcium ion pathway, which in turn manages asthma 61 63 . This may also explain the pleiotropic effects of traditional Chinese medical herbs.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we found that quercetin, kaempferol, and apigenin acted on 172, 106 and 46 targets, respectively, and became the crucial bioactive components in MXGSD. Some studies suggested that quercetin could reduce airway inflammation and relax airway smooth muscle (ASM) by regulating some key pathways, such as mast cell signaling pathway and calcium ion pathway, which in turn manages asthma 61 63 . This may also explain the pleiotropic effects of traditional Chinese medical herbs.…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin could inhibit acetylcholine chloride-induced continuous contractions in human bronchial airway smooth muscle strips, which indicated that quercetin could be developed as a bronchodilator [ 39 ]. Although quercetin has the potential to be a novel medication treating COPD, the safety of quercetin in patients with COPD is still not clear.…”
Section: Roles Of Flavonoids In Clinical Testingmentioning
confidence: 99%
“…Recently, various studies focused on TCM for a safer and milder treatment of pulmonary disease. A plurality of the investigated natural herbal extracts or single compound exert their relaxant effect on precontracted airway muscle [7,8]. Coptisine is a natural compound which displays a broad range of pharmacological actions [11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…However, rigorous Western methodologies should be employed to isolate the effective substances from the complex mixture of chemicals for scientific validation and further clinical application. Our previous studies have revealed that quite a few effective ingredients or extracts of TCM could relax abnormal smooth muscle contraction in pulmonary diseases [7,8].…”
Section: Introductionmentioning
confidence: 99%